Perancangan Aplikasi Animasi Interaktif Japanese Vocabulary Berbasis Android - Widyaa, Syahruni; Amalia, Rizky; Rismayani, Rismayani (MULTINETICS, 2022)
In Indonesia, Japanese is one of the languages that is less attractive. Because Japanese has a lot of vocabulary, it is difficult to learn the language. Therefore, in the research that we are currently doing, we will create and android based application program with an interface that is made as attractive as possible so that people are more interested in learning the language and make it easier to understand. The features provided by this application are the in the form of vocabulary and some games to test how well we understand the material given. In its development used data collection techniques in the form of observation, literature study, and questionnaires. Hopefully in the future this application can be useful and make people interested in the learning Japanese. The application was tested using the blackbox technique.